2021
DOI: 10.3389/fphar.2021.656928
|View full text |Cite
|
Sign up to set email alerts
|

Serum Soluble Tumor Necrosis Factor Receptors 1 and 2 Are Early Prognosis Markers After ST-Segment Elevation Myocardial Infarction

Abstract: Background: As inflammation following ST-segment elevation myocardial infarction (STEMI) is both beneficial and deleterious, there is a need to find new biomarkers of STEMI severity.Objective: We hypothesized that the circulating concentration of the soluble tumor necrosis factor α receptors 1 and 2 (sTNFR1 and sTNFR2) might predict clinical outcomes in STEMI patients.Methods: We enrolled into a prospective cohort 251 consecutive STEMI patients referred to our hospital for percutaneous coronary intervention re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
(31 reference statements)
4
14
1
1
Order By: Relevance
“…When comparing our data to theirs, our control group was younger and with more female donors, and we observed lower levels of sTNFR1 but higher levels of sTNFR2, but in both studies, the sTNFR levels in the patients were significantly higher than in the control group. However, it has to be noted that the levels of sTNFR1 reported by us and others 16 18 in STEMI patients are relatively similar to the ones reported in prospective studies in patients with stable CAD 7 , 8 , 20 , and also to levels reported in population-based studies in older adults 9 , 11 13 . Thus, the level of sTNFR1 may not be of diagnostic interest on the population level in this age group.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…When comparing our data to theirs, our control group was younger and with more female donors, and we observed lower levels of sTNFR1 but higher levels of sTNFR2, but in both studies, the sTNFR levels in the patients were significantly higher than in the control group. However, it has to be noted that the levels of sTNFR1 reported by us and others 16 18 in STEMI patients are relatively similar to the ones reported in prospective studies in patients with stable CAD 7 , 8 , 20 , and also to levels reported in population-based studies in older adults 9 , 11 13 . Thus, the level of sTNFR1 may not be of diagnostic interest on the population level in this age group.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, the level of sTNFR1 may not be of diagnostic interest on the population level in this age group. On the other hand, similar to us, both Vaglimigli et al 17 and Paccalet et al 16 report an increased risk of adverse events in STEMI patients with higher sTNFR1 levels, and Nilsson et al 18 shows associations between levels of sTNFR1 and the final infarct size. Also, the two studies with measurements at different time points 16 , 18 show the same trend as us with increasing levels of sTNFR1 between admission and 24 h, which might indicate a rapid response to the acute event and following intervention which is mirrored in the levels of sTNFR1 released.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…STEMI patients with significantly elevated levels of TNF- α are more likely to have subsequent ischemic events, HF, and all cardiovascular events [ 7 ]. Since TNF- α induces the release of soluble TNF- α receptors 1 and 2 (sTNFR1 and sTNFR2) into the circulation in STEMI patients, these patients with high circulating sTNFR1 or sTNFR2 are at high risk of adverse clinical events [ 83 ]. Furthermore, TNF- α is also involved in adverse remodeling after myocardial infarction [ 84 ].…”
Section: Tnf- α and Chdmentioning
confidence: 99%